Improvement of crop-animal systems in Southeast Asia - Devendra, C. (Khon Kaen University, 2000)
This paper reviews the importance of livestock in the targeted agro-ecological zones of Southeast Asia and description of ILRI's selection of benchmark sites for livestock research.